PENERAPAN SANKSI PIDANA BAGI PENGEDAR MINUMAN KERAS OPLOSAN YANG MENGAKIBATKAN KORBAN JIWA DI WILAYAH HUKUM SURAKARTA - PARWOTO, PARWOTO (Dinamika Hukum, 2015)
Legal research aims to determine the application of criminal sanctions for traffickers adulterated liquor in surakarta. Background research that the impact of liquor encourage crime because the perpetrator is under the influence of alcohol, such as murders, rapes, fights and accidents. government intervention is needed, so this problem can be reduced and controlled so as not to spread everywhere. because itun set of rules governing liquor and health is the basis for control and supervise the distribution of liquor, especially liquor oplosan that spread through the community. This research is a descriptive normative law are contrary to the concept of the law is what was decided by the judge inconcreto and tersistematisasi as the judge made law. the type of data in this research is secondary data. the data collection is done by a search of legal materials of primary, secondary and tertiary. data analysis technique used is the technique of analysis using deductive logic. The results showed that the judge in imposing a criminal into account the elements of criminal acts and aspects of the personality of the accused. consideration was obtained by digging all the information that concern the defendant (the subjective factor) as well as the actions of the defendant (objective factors) through the testimony of witnesses and experts, and other evidences yangb legally valid, so the judges can determine fair and equitable criminal prosecution. Keywords: implementation of criminal sanctions, traffickers adulterated liquor